(untitled) (Journal of Computational Mathematics, 2000)
A finite difference scheme for the generalized nonlinear Schr00f6dinger equation with variable coefficients is developed. The scheme is shown to satisfy two conservation laws. Numerical results show that the scheme is accurate and efficient.